The triangle of microfinance : financial sustainability, outreach, and impact - Meyer, Richard L., 1937-; Zeller, Manfred (Baltimore : The Johns Hopkins University Press, 2002)
The genius of microfinance lies in simple ideas, like group lending, that have made it possible to provide financial services to people previously thought to be unbankable. The book addresses a number of difficult methodological issues faced by analysts of microfinance schemes in assessing effective needs for credit, evaluating outreach, and measuring impact.
International Food Policy Research Institute.
Includes bibliographical references and index.
nmn 11/06/13
Loans
Keywords: Microfinance